Open source cloud computing systems : practices and pradigms - Caceres, Juan , 1973-; Hierro, Juan J. , 1966-; Vaquero, Luis M. (IInformation Science Reference, 2012)
"This book bridges the gap between solutions and users' needs pertaining to the most relevant open source cloud technologies available today from a practical perspective" -- Provided by publisher